Commonality in Liquidity: Evidence from Emerging Asian Actively-Managed Equity Funds - Suresh Kumar; Eliza Nor; Nik Hadiyan Nik Azman; Hyder Ali (Asian Academy of Management Journal of Accounting and Finance, 2023)
In this study, a set of common factors of liquidity that had previously been recorded at the equity security level is examined for its effect on inter and intra-market liquidity variations in equity funds in emerging Asian markets. Cross-market liquidity co-movement between the fund’s portfolio and the market portfolio, which typically measures systematic liquidity risk and market integration, is the liquidity commonality for mutual funds. This research builds on Wang Jianxin’s study in 2013 by including market liquidity, return and volatility as common factors of liquidity, and the partial R2 of the common factors reveals each factor’s contribution. We find that emerging Asian countries share 24.14% of the intra-market liquidity commonality between funds and equity markets, and market liquidity is tied to such relationship. Emerging Asian region share 2.76% of inter-market liquidity commonality and regional market return and volatility majorly contribute to this liquidity commonality. The significance of domestic financial markets is evidenced by the wide disparity in liquidity commonality between domestic and regional markets.